Living in a challenging environment: Monitoring stress ecology by non-destructive methods in an Antarctic seabird - Olmastroni, Silvia (2024)
How Antarctic species are facing historical and new stressors remains under-surveyed and risks to wildlife are still largely unknown. Adélie penguins Pygoscelis adeliae are well-known bioindicators and sentinels of Antarctic ecosystem changes, a true canary in the coal mine. Immuno-haematological parameters have been proved to detect stress in wild animals, given their rapid physiological response that allows them tracking environmental changes and thus inferring habitat quality. Here, we investigated variation in Erythrocyte Nuclear Abnormalities (ENAs) and White Blood Cells (WBCs) in penguins from three clustered colonies in the Ross Sea, evaluating immuno-haematological parameters according to geography, breeding stage, and individual penguin characteristics such as sex, body condition and nest quality. Concentrations of mercury (Hg) and stable isotopes of carbon and nitrogen (as proxies of the penguin´s trophic ecology) were analysed in feathers to investigate the association between stress biomarkers and Hg contamination in Adélie penguins. Colony and breeding stage were not supported as predictors of immuno-haematological parameters. ENAs and WBCs were respectively ∼30 % and ∼20 % higher in male than in female penguins. Body condition influenced WBCs, with penguins in the best condition having a ∼22 % higher level of WBCs than those in the worst condition. Nest position affected the proportion of micronuclei (MNs), with inner-nesting penguins having more than three times the proportion of MNs than penguins nesting in peripheral positions. Heterophils:Lymphocytes (H:L) ratio was not affected by any of the above predictors. Multiple factors acting as stressors are expected to increase prominently in Antarctic wildlife in the near future, therefore extensive monitoring aimed to assess the health status of penguin populations is mandatory.